Primary health care financing interventions: a systematic review and stakeholder-driven research agenda for the Asia-Pacific region. (16th August 2019) - Angell, Blake; Dodd, Rebecca; Palagyi, Anna; Gadsden, Thomas; Abimbola, Seye; Prinja, Shankar; Jan, Stephen; Peiris, David
Abstract : Introduction: Interventions targeting the financing of primary health care (PHC) systems could accelerate progress towards universal health coverage; however, there is limited evidence to guide best-practice implementation of these interventions. This study aimed to generate a stakeholder-led research agenda in the area of PHC financing interventions in the Asia-Pacific region. Methods: We adopted a two-stage process: (1) a systematic review of financing interventions targeting PHC service delivery in the Asia-Pacific region was conducted to develop an evidence gap map and (2) an electronic-Delphi (e-Delphi) exercise with key national PHC stakeholders was undertaken to prioritise these evidence needs. Results: Thirty-one peer-reviewed articles (including 10 systematic reviews) and 10 grey literature reports were included in the review. There was limited consistency in results across studies but there was evidence that some interventions (removal of user fees, ownership models of providers and contracting arrangements) could impact PHC service access, efficiency and out-of-pocket cost outcomes. The e-Delphi exercise highlighted the importance of contextual factors and prioritised research in the areas of: (1) interventions to limit out-of-pocket costs; (2) financing models to enhance health system performance and maintain PHC budgets; (3) the design of incentives to promote optimal care without unintended consequences and (4) the comparative effectiveness of different PHC service delivery strategies using local data. Conclusion: The research questions which were deemed most important by stakeholders are not addressed in the literature. There is a need for more research on how financing interventions can be implemented at scale across health systems. Such research needs to be pragmatic and balance academic rigour with practical considerations.